Investigation of thermo-mechanical behaviour in incremental sheet forming - Qin, Zhenyuan (2025)
Incremental sheet forming (ISF) is an emerging flexible sheet forming process that has shown considerable advantages in manufacturing small batch or customised sheet products due to its high adaptability and reduced tooling costs. The principle of ISF is to use a computer numerical control (CNC) milling machine or a robotic system to control a hemispheric tool moving along a predefined tool path to progressively form the blank sheet into the desired shape. Conventional ISF is usually conducted at room temperature and hence exhibits limitations in manufacturing of hard-to-deform materials, e.g., magnesium and titanium alloys due to poor ductility at room temperature. To overcome this difficulty, heat-assisted ISF has been developed to further improve forming limit of hard-to-deform materials. Based on the heating source used, heat-assisted ISF can be divided into two categories, one is heat-assisted ISF by adopting an external heat source including electrical, laser, induction and hot air heating, while the other is so-called frictional stir incremental forming (FSIF), where the heating is generated by tool-workpiece interaction and frictional heat largely due to the ISF tool rotation.